De dochters van Marianne : 75 jaar SVV - De Weerdt, Denise; Peiren, Luc; Bracke, Nele; Vanrie, Stiene; Celis, Karen; Hoedemaeckers, Caroline; Lievyns, Luc (Antwerpen-Baarn: Hadewijch; Gent: Amsab, 1997)
"Denise De Weedt (red.) ; voorwoord: Leona Detiège ; bijdragen van Luc Peiren, Nele Bracke, Stiene Vanrie, Caroline Hoedemaeckers, Karen Celis en Luc Lievyns ; nawoord: Hetty Geldolf"